2013
DOI: 10.2139/ssrn.2337207
|View full text |Cite
|
Sign up to set email alerts
|

Is Working Capital Management Value-Enhancing? Evidence from Firm Performance and Investments

Abstract: This paper examines the value effect of working capital management (WCM) for a large sample of US firms over the period 1982-2011. Taking into account omitted variables and reverse causality, we show that the decrease in working capital across time leads to increasing performance. This relationship is driven by firms that have substantial cash unnecessarily tied up in working capital. Importantly, we also show that corporate investment is the channel through which improvement in WCM translates into superior pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
278
8
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(329 citation statements)
references
References 70 publications
(91 reference statements)
34
278
8
9
Order By: Relevance
“…Though, previous studies (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;Kieschnick et al, 2013;Wang, 2002;Wasiuzzaman, 2015) have focus on the impact of WCM and its components (i.e. account receivables, account payables and inventory holding) on firm value, however, there is need for more studies to concentrate on large firms due to their vulnerabilities of managing working capital in recent years and because most large firms have a tendency of having a large amount of cash invested in working capital, and considerable amounts of short-term payables, as a basis of financing (Deloof, 2003).…”
Section: Working Capital Management and Firm Valuementioning
confidence: 90%
See 2 more Smart Citations
“…Though, previous studies (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;Kieschnick et al, 2013;Wang, 2002;Wasiuzzaman, 2015) have focus on the impact of WCM and its components (i.e. account receivables, account payables and inventory holding) on firm value, however, there is need for more studies to concentrate on large firms due to their vulnerabilities of managing working capital in recent years and because most large firms have a tendency of having a large amount of cash invested in working capital, and considerable amounts of short-term payables, as a basis of financing (Deloof, 2003).…”
Section: Working Capital Management and Firm Valuementioning
confidence: 90%
“…While some studies found a negative relationship between WCM and firm value (e.g., Aktas et al, 2015;Autukaite & Molay, 2013;De Almeida & Eid jr, 2014;Kieschnick et al, 2008;Kieschnick et al, 2013;Lifland, 2011;Mohamad & Saad, 2010;Wasiuzzaman, 2015), others found a positive relationship (e.g., Abuzayed, 2012;Ali & Ali, 2012;Lyroudi & Lazaridis, 2000;Rimo & Panbunyuen, 2010). Varying explanation has been given by different researchers on the direction of the relationship between WCM and firm value.…”
Section: Working Capital Management and Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study show that firms have an optimal working capital level and divergence from this level harms to the stock and operating performance of the firms. The authors also documented that working capital management increases corporate performance through corporate investment channel [14].…”
Section: Literature Reviewmentioning
confidence: 94%
“…However, holding too much cash suggests that this part of the resources is not involved in the profit-making of firms to generate corresponding performance [50]. As a result, the fourth hypothesis is made for CHR as follows:…”
Section: Vector Of Operational Capacitymentioning
confidence: 99%